Longyearbyen Lagoon (Spitsbergen): Gravel Spits Movement Rate and Mechanisms - Nataliya Marchenko; Aleksey Marchenko (Geographies)
Understanding lagoon behavior is crucial for both scientific research and engineering decisions, especially in delicate Arctic environments. Lagoons are vital to coastal areas, often bolstering infrastructure resilience. Since spring 2019, we have monitored the Longyearbyen lagoon (Spitsbergen), vital for coastal erosion defense and serving as a natural laboratory. The location’s well-developed infrastructure and accessible logistics make it an ideal testing site available at any time. It can be used for many natural scientific studies. The lagoon continually changes due to the primary action of waves and tides. This article focuses on gravel spit movement, accelerating in recent years to several meters monthly. Using methods of aerial and satellite images, laser scanning, and hydrodynamic measurements, we have delineated processes, rates, and mechanisms behind this movement. The measurements revealed an accelerating eastward movement of the lagoon spit, from 8 m in the first year to 86 m in the fourth year of observation. This can be explained by a combination of the reconstruction of the Longyearbyen riverbed and increased flow because of climate change. Notably, the expansion does not only occur in the summer months: from September 2022 to February 2023, the spit moved by 40 m, and then, by 19 m from February to June 2023. We found that the bed-load transport along the spit coupled with gravel slides are the primary drives of lagoon expansion and growth. We also investigated movements of groundwater in the spit and changes in gravel contents along the spit, influencing the water saturation of the gravel. Modelling these processes aids in forecasting lagoon system development, crucial for informed management and engineering decisions in Arctic coastal regions.